Gas chromatography - mass spectrometry system applied to determine botanical origin of various types of edible vegetable oils - Pastor Kristian; Vujasinović Vesna; Marjanović-Jeromela Ana; Vujić Đura; Jovanović Đorđe; Ačanski Marijana (Journal of the Serbian Chemical Society, 2019)
This study represents a new strategy for discrimination of 59 samples of various cold-pressed, virgin and refined edible vegetable oils according to the corresponding botanical origin. Samples were produced from 17 plant species: olive, sunflower, safflower, flax, pumpkin, sesame, hemp, walnut, hazelnut, almond, grape, black cumin, apricot, plum, soybean, wheat and rapeseed. A GC/MS device performing in a ion current (IC) mode, combined with multivariate clustering, was employed in the analysis. Derivatization reaction occurred in the injector of a gas chromatograph. The discriminations between species were based on marker-peaks of 9 molecular ions of dominant fatty acid methyl esters (FAMEs), which were chosen as descriptors: m/z 268, 270, 292, 294, 296, 298, 324, 326 and 354. Dendrogram obtained after performing cluster analysis shows clear discriminations of the analyzed samples, based on the belonging botanical origin. These results demonstrate that IC-GC/MS approach with cluster analysis could be a useful tool in rapid screening for botanical origin of commercial samples of various edible vegetable oils.